Killing animals - Animal Studies Group (University of Illinois Press, 2006)
With killing representing the ultimate expression of human power over animals, this book reveals the complexity of the phenomenon by exploring the extraordinary diversity in killing practices and the wide variety of meanings attached to them. It examines aspects of the role of animals in human societies, from the 17th century to the present day.
Keywords: Animal welfare; Hunting; Slaughtering and slaughter-houses; Human-animal relationships; ihminen-eläinsuhde; eläinten hyvinvointi; eläimet; metsästys; tappaminen; teurastamot; människa-djurförhållande; djurs välbefinnande; djur; jakt; dödande; slakterier